2016
DOI: 10.1039/c6nr02151d
|View full text |Cite
|
Sign up to set email alerts
|

Analysing intracellular deformation of polymer capsules using structured illumination microscopy

Abstract: Understanding the behaviour of therapeutic carriers is important in elucidating their mechanism of action and how they are processed inside cells. Herein we examine the intracellular deformation of layer-by-layer assembled polymer capsules using super-resolution structured illumination microscopy (SIM). Spherical- and cylindrical-shaped capsules were studied in three different cell lines, namely HeLa (human epithelial cell line), RAW264.7 (mouse macrophage cell line) and differentiated THP-1 (human monocyte-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Previous studies have shown that soft polymeric capsules inside cells are deformed upon ingestion because of the mechanical stress exerted by the cell membrane. [ 42,43 ] The acquired images suggest that RAW264.7 cells can exert high shear forces on CpG cap during their internalization. As CpG cap are highly hydrated, hollow, and flexible, they are prone to deformation upon internalization.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that soft polymeric capsules inside cells are deformed upon ingestion because of the mechanical stress exerted by the cell membrane. [ 42,43 ] The acquired images suggest that RAW264.7 cells can exert high shear forces on CpG cap during their internalization. As CpG cap are highly hydrated, hollow, and flexible, they are prone to deformation upon internalization.…”
Section: Resultsmentioning
confidence: 99%
“…A relevant example is the particle deformation following internalization due to mechanical stress. Caruso and coworkers reported on the use of SIM to image the deformation of polymer capsules occurring inside cells 135 . Hollow spheres are more susceptible to mechanical stress and a high degree of compression was observed in different cell lines irrespective of the capsule shape, suggesting that the forces are cell-dependent.…”
Section: [H2] Cellular Trafficking and Localizationmentioning
confidence: 99%
“…As an example, structure illumination microscopy (SIM) has been used to monitor particle deformation during internalization. 40 Interestingly, different cell lines exert different mechanical forces, inducing a proportional polymer capsule’s shrinkage. Moreover, the stability of supramolecular aggregates in serum and in cells can be followed by STORM, revealing in what state (assembled or disassembled) the carriers reach different locations.…”
Section: Not Only Where But Also Howmentioning
confidence: 99%